THE HISTORIY OF THE MASJID RAYA KOTA PEKANBARU - Ahmad, Ali Ahmad; Saiman, Marwoto Saiman; Melay, Ridwan Melay (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract, begins from Siak kingdom center in Mempura. After Alamuddinsyah appointed king of Siak IV in 1761 with the title of Sultan Abdul Jalil Alamudinsyah. As Sultan Alamuddinsyah reson to move the center of kingdom Siak to Senapelan that The Dutch do not interferen in the administration of Siak and unaffected kingdom of The Netherlands. In 1766, Alamuddinsyah died and was replaced by Sultan Yahya Abdul Jalil Muzafar Syah. At this time Senapelan handed to four Datuk by Suku Lima Puluh, Pesisir, Tanah Datar dan Kampar. After Sultan Yahya died and was replaced by the king young Ali, he returned to Senapelan to pass on his father ideals and established the Sultan Alamuddinsayah a week on 21 Rajab 1204 H and Tuesday, June 23, 1784 M. Now know as the birthday of the city Peknbaru is celebrated June 23. In the early days of the removal of the royal Siak in the year 1761 there has been a Suarau/Mosque is thought to have been there standing around the Kingdom after the king Alamuddinsyah Siak put his kingdom in Senapelan center adjacent to the mosque are now better known as the grand mosque in Pekanbaru. Surau/mosque is right at the royal palace environmen Siak in Senapelan/Pekanbaru previously. The mosque is also a witness of the kingdom center in Senapelan Siak. Near the mosque there is also the tomb of the Sultan of Siak king and the royal familiy. In the graveyard there Marhum Bukit of the kinh’s Hill Alamuddinsyah and Marhum Pekan is the king young Ali.The results of this study indicate that the grand mosque in Senapelan/Pekanbaru adjacent to the center of kingdom of Siak and in the Palace, also known as the oldest mosque in the city of Pekanbaru and became one of the founding witness empire Siak inSenapelan once or known as the city of Pekanbaru.   Keywords: The History of the Masjid Raya kota Pekanbaru.